A Real Chance for the Transatlantic Partnership on Climate Policy - Claudia Kemfert (Intereconomics, 2021)
The new transatlantic partnership can be the cornerstone of this change: real climate protection without false truths and hidden smoke bombs, but a shift to a full supply of renewable energies.
Keywords: 330; Klimapolitik; USA